PEM hydrogen production membrane electrode assembly and preparation method thereof
By optimizing the structural design of the membrane electrode assembly and the modification of UV glue, the problem of proton membrane being easily punctured and leaked during the assembly process is solved, and the safety and performance of the membrane electrode assembly are improved.
Patent Information
- Application Number
- CN202510098964.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-03-14
AI Technical Summary
During the assembly process, existing PEM hydrogen-making membrane electrode components are prone to problems such as proton membrane being broken, air leakage and not being tightly bonded, which affects the safety, performance and service life of the components.
By designing the dimensional relationship between the cathode gasket and the anode gasket, the proton membrane is evenly distributed in the assembly, the membrane electrode gap is filled with modified UV glue, and the high intensity and stability of the glue is ensured through hot pressing and ultraviolet curing techniques. At the same time, the anode titanium porous transport layer is in direct contact with the proton membrane and is designed through frame support and misalignment superposition to reduce the risk of air leakage.
The thickness uniformity and bonding strength of the membrane electrode assembly are improved, reducing the risk of proton membrane being punctured and leaking, and improving the safety and performance of the assembly.
Smart Images

Figure CN119615225A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of PEM hydrogen production membranes, and in particular to a PEM hydrogen production membrane electrode assembly and a preparation method thereof. Background Art
[0002] PEM water electrolysis hydrogen production technology uses proton membrane as a solid electrolyte, pure water as a reactant, and the products are hydrogen and oxygen. Unlike proton membrane fuel cells, PEM hydrogen production electrolyzers need to output high-purity hydrogen at a certain pressure, so the membrane electrode generally needs to use a thicker proton membrane. However, in the related technology, the size of the proton membrane in the membrane electrode is smaller than the membrane electrode, which will cause height differences at different positions of the membrane electrode, resulting in debonding of the membrane electrode, difficulty in sealing the electrolyzer plate and the membrane electrode, etc., which affects the use, safety and performance of the membrane electrode assembly.
[0003] During the assembly process of the PEM electrolyzer, a titanium porous transport layer needs to be stacked on each side of the membrane electrode. The edge of the titanium porous transport layer can easily puncture the proton membrane, causing the electrolyzer to leak and fail, and even cause safety accidents.
[0004] In addition, during the UV glue filling process, traditional UV glue does not have high temperature resistance and insulation properties, and is accompanied by problems such as slow curing and low viscosity, which makes it easy to cause melting or bubbles under high temperature conditions, resulting in insufficient bonding, indirectly affecting the performance of the PEM hydrogen membrane electrode assembly.
[0005] In summary, it is of great significance to obtain a PEM hydrogen production membrane electrode assembly and a preparation method thereof. Summary of the invention
[0006] The object of the present invention is to provide a PEM hydrogen production membrane electrode assembly and a preparation method thereof to solve the problems raised in the prior art.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A PEM hydrogen production membrane electrode assembly comprises an anode gasket, a cathode gasket, a proton membrane, and UV glue; the proton membrane is arranged between the anode gasket and the cathode gasket; the cathode gasket comprises a cathode gasket outer frame and a cathode gasket inner frame; the anode gasket comprises an anode gasket outer frame and an anode gasket inner frame.
[0009] More optimally, the size of the cathode gasket inner frame is larger than the proton membrane; the size of the anode gasket inner frame is smaller than the proton membrane.
[0010] More optimally, a method for preparing a PEM hydrogen production membrane electrode assembly comprises the following steps:
[0011] Step 1: Cut the base membrane according to the size of the proton membrane to obtain a cathode gasket and an anode gasket for standby use;
[0012] Step 2: stack the cathode gasket, the proton membrane, and the anode gasket, and hot-press at 100 to 150° C. for 30 to 120 seconds to obtain a membrane electrode;
[0013] Step 3: Fill the membrane electrode with UV glue and solidify it to form a glue layer; then tightly connect the anode titanium porous transport layer and the cathode titanium porous transport layer to the proton membrane on both sides of the proton membrane to assemble the electrolyzer to obtain a PEM hydrogen production membrane electrode assembly.
[0014] Preferably, the material of the base film includes one of polyimide, polyethylene terephthalate, polyethylene naphthalate, and polyphenylene sulfide.
[0015] More optimally, the preparation process of the assembled electrolytic cell is as follows: after the glue layer is formed, the anode titanium porous transport layer is in direct contact with the proton membrane and is compressed evenly, the edge of the anode titanium porous transport layer is supported by a frame, and the cathode titanium porous transport layer and the anode titanium porous transport layer are staggered and superimposed.
[0016] More optimally, the specific preparation process of the UV glue is:
[0017] Step 1: (1) adding silicon nitride and 4-aminobutyltriethoxysilane to a 40-50 wt% ethanol aqueous solution and mixing them evenly, then adding isocyanoethyl methacrylate and reacting them at 25-35° C. for 2-3 hours; washing and drying to obtain modified silicon nitride; (2) adding modified silicon nitride, perfluoroalkylethyl acrylate, methyl methacrylate, N-vinyl carbazole, 3-[tri(trimethylsiloxy)silyl]propyl methacrylate, 2-acrylic acid, 6-[4-(trans-4-pentylcyclohexyl)phenoxy]hexyl ester, azobisisobutyronitrile, octylphenol polyoxyethylene ether, and sodium dodecyl sulfate to toluene, reacting them at 70-80° C. for 5-6 hours to obtain a heat-resistant added filler;
[0018] Step 2: Add polyurethane acrylate, heat-resistant additive filler, mercapto silicone resin, polypropylene glycol diglycidyl ether, acryloxy triisopropyl silane, and cyclohexyl diphenyl ketone to tetrahydrofuran, and stir evenly in a dark place to obtain UV glue.
[0019] More optimally, the specific process of the curing process is: after the membrane electrode is filled with UV glue, it reacts at 30-50° C. for 5-6 hours under ultraviolet light.
[0020] More optimally, the raw materials of the UV glue include the following components: by mass, 60 to 70 parts of polyurethane acrylate, 15 to 22 parts of heat-resistant added filler, 8 to 10 parts of mercapto silicone resin, 1 to 2 parts of polypropylene glycol diglycidyl ether, 1 to 2 parts of acryloxytriisopropylsilane, 0.1 to 0.3 parts of cyclohexyl diphenyl ketone, and 150 to 180 parts of tetrahydrofuran.
[0021] In a further scheme, the specific preparation process of the mercapto silicone resin is: add γ-mercaptopropyltrichlorosilane and trimethylchlorosilane in a mass ratio of 2:0.8-1.2 to a 10-20wt% isopropanol aqueous solution, stir at 0-10°C for 1-1.5 hours, then react at 25-40°C for 1-3 hours, add isododecane for extraction, purify, filter and dry to obtain the mercapto silicone resin.
[0022] More optimally, the raw materials of the modified silicon nitride include the following components: 3 to 4 parts of silicon nitride, 1 to 2 parts of 4-aminobutyltriethoxysilane, 30 to 40 parts of 40 to 50 wt% ethanol aqueous solution, and 1 to 2 parts of isocyanoethyl methacrylate, by weight;
[0023] The raw materials of the heat-resistant additive filler include the following components: by mass, 15 parts of modified silicon nitride, 5 to 6 parts of perfluoroalkylethyl acrylate, 1 to 2 parts of methyl methacrylate, 2 to 3 parts of N-vinyl carbazole, 5 to 6 parts of 3-[tris(trimethylsiloxy)silyl]propyl methacrylate, 4 to 5 parts of 2-acrylic acid, 6-[4-(trans-4-pentylcyclohexyl)phenoxy]hexyl ester, 0.2 to 0.5 parts of azobisisobutyronitrile, 0.5 to 1 parts of octylphenol polyoxyethylene ether, 0.5 to 1 parts of sodium dodecyl sulfate, and 100 to 120 parts of toluene.
[0024] In a further scheme, when the membrane electrode of the present invention is used to assemble an electrolytic cell, the anode titanium porous transport layer is in direct contact with the proton membrane and is evenly compressed, thereby reducing the contact impedance. The edge of the anode titanium porous transport layer is supported by a frame, and the cathode and anode titanium porous transport layers are staggered and superimposed, thereby reducing the risk of the proton membrane being punctured and leaking.
[0025] In the scheme, the UV glue prepared by compounding different components has high temperature resistance, insulation performance, high stability, high strength, high viscosity and high transmittance.
[0026] Among them, in the PEM hydrogen production process, due to the exothermic effect of the electrochemical reaction, a certain amount of heat will accumulate inside the component. Ordinary UV glue cannot withstand high temperatures and will melt. It cannot tightly fill and seal the gap between the anode gasket and the proton membrane, thereby affecting the conductivity of the proton membrane and the activity of the catalyst, and affecting the reaction rate of the electrolyzer. Therefore, in order to improve the high temperature resistance of UV glue, the solution adopts a composite component, introduces fluorine, nitrogen, silicon and other elements, enhances the high temperature resistance, prevents failure due to high temperature during use, and improves the quality of UV glue.
[0027] Among them, ordinary UV glue does not have insulation properties, which will cause the proton membrane to be affected by current or voltage during the PEM hydrogen production process, resulting in a decrease in performance. Therefore, in order to improve the insulation performance, the scheme introduces silicon nitride as an inorganic filler, which itself has high temperature resistance and insulation properties. After the amino group is modified, it reacts with isocyanate to further obtain a substance with a structure similar to polyurethane acrylate, which is filled into the gaps of the network to further improve stability and high transmittance.
[0028] Among them, free radical modification and cross-linking are used to form a three-dimensional network structure of silicone, and mercapto groups, epoxy groups, and polypropylene glycol diglycidyl ether are introduced to further improve the uniformity of distribution of each component and make them fully react with each other, so as to improve stability, high transmittance and adhesion. During use, the prepared UV glue can maintain high fluidity while being able to quickly absorb ultraviolet light to form a solidification, avoiding the generation of bubbles that affect the use effect, while enhancing the bonding effect.
[0029] In addition, adding substances such as ether and benzene rings can further improve the hardness and mechanical properties of UV glue and improve its quality.
[0030] In a further embodiment, the UV glue has a high temperature resistance exceeding 100° C. and does not melt or become ineffective.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The present invention proposes a membrane electrode assembly with uniform thickness, which avoids the height difference at different positions of the membrane electrode due to the thick proton membrane; the present invention uses UV glue to fill the gap, and the UV glue has a certain fluidity before curing, which further ensures the uniformity of thickness, and improves the bonding strength after the UV glue is cured; when the membrane electrode of the present invention is used to assemble the electrolyzer, the anode titanium porous transmission layer is in direct contact with the proton membrane, and the compression is uniform, which reduces the contact impedance. The edge of the anode titanium porous transmission layer is supported by a frame, and the anode and cathode titanium porous transmission layers are staggered and superimposed, which reduces the risk of the proton membrane being punctured and leaking. The use of the present invention can improve the safety and performance of the membrane electrode assembly from the above aspects. The present invention has a simple structure, is easy to operate, saves membrane electrode materials, reduces processing difficulty, and can effectively reduce the cost of the membrane electrode.
[0033] (2) The UV glue prepared by the present invention has high temperature resistance, insulation performance, high stability, high strength, high adhesion and high transmittance. It can maintain high fluidity, can quickly absorb ultraviolet light to form solidification, and avoid the generation of bubbles that affect the use effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0035] Figure 1 This is a diagram of a PEM hydrogen production membrane electrode assembly;
[0036] Figure 2 This is a partial side view of the PEM hydrogen production membrane electrode assembly;
[0037] Figure 3 This is a structural breakdown diagram of the PEM hydrogen production membrane electrode assembly;
[0038] Figure 4 This is a partial side view of the PEM hydrogen production membrane electrode assembly electrolyzer after assembly. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] It should be noted that the following parts are by mass, and all raw materials involved in the present invention are purchased from manufacturers without any special restrictions, and exemplarily include: in the following embodiments, the product number of silicon nitride is S817700-10g; the CAS number of 3-[tris(trimethylsiloxy)silyl]propyl methacrylate is 17096-07-0; the CAS number of 2-acrylic acid, 6-[4-(trans-4-pentylcyclohexyl)phenoxy]hexyl ester is 586417-49-4.
[0041] In the following embodiments, it is particularly noted that the relevant material parameters are as follows:
[0042] (1) The material of the base film is PI.
[0043] (2) Fill the space between the anode gasket and the proton membrane inside the membrane electrode with UV glue, and after curing, form a glue layer. The type of the glue layer is thermosetting glue, and the material of the glue layer is polyurethane or acrylic.
[0044] (3) The structure of the PEM hydrogen production membrane electrode assembly includes an anode gasket, a cathode gasket, a proton membrane, and UV glue; the proton membrane is arranged between the anode gasket and the cathode gasket; the cathode gasket includes a cathode gasket outer frame and a cathode gasket inner frame; the anode gasket includes an anode gasket outer frame and an anode gasket inner frame.
[0045] (4) The size of the cathode gasket inner frame is larger than the proton membrane; the size of the anode gasket inner frame is smaller than the proton membrane.
[0046] Embodiment 1: A method for preparing a PEM hydrogen production membrane electrode assembly, comprising the following steps:
[0047] Step 1: Cut the base membrane according to the size of the proton membrane to obtain a cathode gasket and an anode gasket for standby use;
[0048] Step 2: stack the cathode gasket, the proton membrane, and the anode gasket, and perform hot pressing at a pressure of 0.3 MPa and a temperature of 125° C. for 75 seconds to obtain a membrane electrode;
[0049] Step 3: After filling the membrane electrode with UV glue, react at 40°C for 5.5 hours under ultraviolet light to form a glue layer; then the anode titanium porous transport layer is in direct contact with the proton membrane and compressed evenly. The edge of the anode titanium porous transport layer is supported by a frame, and the cathode titanium porous transport layer and the anode titanium porous transport layer are staggered and superimposed to obtain a PEM hydrogen production membrane electrode assembly.
[0050] Embodiment 2: A method for preparing a PEM hydrogen production membrane electrode assembly, comprising the following steps:
[0051] Step 1: (1) Add 3.5 parts of silicon nitride and 1.5 parts of 4-aminobutyl triethoxysilane to 35 parts of 45wt% ethanol aqueous solution and mix well, then add 1.5 parts of isocyanoethyl methacrylate and react at 30°C for 2.5 hours; wash and dry to obtain modified silicon nitride; (2) Add 15 parts of modified silicon nitride, 5.5 parts of perfluoroalkylethyl acrylate, 1.5 parts of methyl methacrylate, 2.5 parts of N-vinyl carbazole, 5.5 parts of 3-[tri(trimethylsiloxy)silyl]propyl methacrylate, 4.5 parts of 2-acrylic acid, 6-[4-(trans-4-pentylcyclohexyl)phenoxy]hexyl ester, 0.35 parts of azobisisobutyronitrile, 0.8 parts of octylphenol polyoxyethylene ether, 0. 8 parts of sodium dodecyl sulfate are added to 110 parts of toluene, and reacted at 75°C for 5.5 hours to obtain a heat-resistant additive filler; (3) γ-mercaptopropyltrichlorosilane and trimethylchlorosilane are added to a 16wt% isopropanol aqueous solution in a mass ratio of 2:1, stirred at 5°C for 1.2 hours, and then reacted at 33°C for 2 hours, and isomeric dodecane is added for extraction, purification, filtration and drying to obtain a mercapto silicone resin; (4) 65 parts of polyurethane acrylate, 18 parts of heat-resistant additive filler, 9 parts of mercapto silicone resin, 1.5 parts of polypropylene glycol diglycidyl ether, 1.5 parts of acryloxytriisopropylsilane, and 0.2 parts of cyclohexyl diphenyl ketone are added to 165 parts of tetrahydrofuran, and stirred evenly in the dark to obtain a UV glue;
[0052] Step 2: Cut the base membrane according to the size of the proton membrane to obtain a cathode gasket and an anode gasket for standby use;
[0053] Step 3: stack the cathode gasket, the proton membrane, and the anode gasket, and perform hot pressing at a pressure of 0.3 MPa and a temperature of 125° C. for 75 seconds to obtain a membrane electrode;
[0054] Step 4: After the membrane electrode is filled with UV glue, it is reacted at 40°C for 5.5 hours under ultraviolet light to form a glue layer; then the anode titanium porous transport layer is in direct contact with the proton membrane and compressed evenly. The edge of the anode titanium porous transport layer is supported by a frame, and the cathode titanium porous transport layer and the anode titanium porous transport layer are staggered and superimposed to obtain a PEM hydrogen production membrane electrode assembly.
[0055] Embodiment 3: A method for preparing a PEM hydrogen production membrane electrode assembly, comprising the following steps:
[0056] Step 1: (1) adding 3.5 parts of silicon nitride and 1.5 parts of 4-aminobutyl triethoxysilane to 35 parts of 45 wt% ethanol aqueous solution and mixing evenly, then adding 1.5 parts of isocyanoethyl methacrylate and reacting at 30°C for 2.5 hours; washing and drying to obtain modified silicon nitride; (2) adding 15 parts of modified silicon nitride, 5.5 parts of perfluoroalkylethyl acrylate, 1.5 parts of methyl methacrylate, 2.5 parts of N-vinyl carbazole, 5.5 parts of 3-[tri(trimethylsiloxy)silyl]propyl methacrylate, 4.5 parts of 2-acrylic acid, 6-[4-(trans-4-pentylcyclohexyl)phenoxy]hexyl ester, 0.35 parts of azobisisobutyronitrile, 0.8 parts of octylphenol polyoxyethylene ether, 0. .8 parts of sodium dodecyl sulfate are added to 110 parts of toluene, and reacted at 75°C for 5.5 hours to obtain a heat-resistant additive filler; (3) γ-mercaptopropyltrichlorosilane and trimethylchlorosilane are added to a 16wt% isopropanol aqueous solution in a mass ratio of 2:0.8, stirred at 5°C for 1.2 hours, and then reacted at 33°C for 2 hours, and isomeric dodecane is added for extraction, purification, filtration and drying to obtain a mercapto silicone resin; (4) 60 parts of polyurethane acrylate, 15 parts of heat-resistant additive filler, 8 parts of mercapto silicone resin, 1 part of polypropylene glycol diglycidyl ether, 1 part of acryloxytriisopropylsilane, and 0.1 part of cyclohexyl diphenyl ketone are added to 150 parts of tetrahydrofuran, and stirred evenly in the dark to obtain UV glue;
[0057] Step 2: Cut the base membrane according to the size of the proton membrane to obtain a cathode gasket and an anode gasket for standby use;
[0058] Step 3: stack the cathode gasket, the proton membrane, and the anode gasket, and perform hot pressing at a pressure of 0.1 MPa and a temperature of 100° C. for 30 seconds to obtain a membrane electrode;
[0059] Step 4: After the membrane electrode is filled with UV glue, it is reacted at 40°C for 5.5 hours under ultraviolet light to form a glue layer; then the anode titanium porous transport layer is in direct contact with the proton membrane and compressed evenly. The edge of the anode titanium porous transport layer is supported by a frame, and the cathode titanium porous transport layer and the anode titanium porous transport layer are staggered and superimposed to obtain a PEM hydrogen production membrane electrode assembly.
[0060] Embodiment 4: A method for preparing a PEM hydrogen production membrane electrode assembly, comprising the following steps:
[0061] Step 1: (1) adding 3.5 parts of silicon nitride and 1.5 parts of 4-aminobutyl triethoxysilane to 35 parts of 45 wt% ethanol aqueous solution and mixing evenly, then adding 1.5 parts of isocyanoethyl methacrylate and reacting at 30°C for 2.5 hours; washing and drying to obtain modified silicon nitride; (2) adding 15 parts of modified silicon nitride, 5.5 parts of perfluoroalkylethyl acrylate, 1.5 parts of methyl methacrylate, 2.5 parts of N-vinyl carbazole, 5.5 parts of 3-[tri(trimethylsiloxy)silyl]propyl methacrylate, 4.5 parts of 2-acrylic acid, 6-[4-(trans-4-pentylcyclohexyl)phenoxy]hexyl ester, 0.35 parts of azobisisobutyronitrile, 0.8 parts of octylphenol polyoxyethylene ether, 0. .8 parts of sodium dodecyl sulfate are added to 110 parts of toluene, and reacted at 75°C for 5.5 hours to obtain a heat-resistant additive filler; (3) γ-mercaptopropyltrichlorosilane and trimethylchlorosilane are added to a 16wt% isopropanol aqueous solution in a mass ratio of 2:1.2, stirred at 5°C for 1.2 hours, and then reacted at 33°C for 2 hours, and isomeric dodecane is added for extraction, purification, filtration and drying to obtain a mercapto silicone resin; (4) 70 parts of polyurethane acrylate, 22 parts of heat-resistant additive filler, 10 parts of mercapto silicone resin, 2 parts of polypropylene glycol diglycidyl ether, 2 parts of acryloxytriisopropylsilane, and 0.3 parts of cyclohexyl diphenyl ketone are added to 180 parts of tetrahydrofuran, and stirred evenly in the dark to obtain a UV glue;
[0062] Step 2: Cut the base membrane according to the size of the proton membrane to obtain a cathode gasket and an anode gasket for standby use;
[0063] Step 3: stack the cathode gasket, the proton membrane, and the anode gasket, and perform hot pressing at a pressure of 0.5 MPa and a temperature of 150° C. for 120 seconds to obtain a membrane electrode;
[0064] Step 4: After the membrane electrode is filled with UV glue, it is reacted at 40°C for 5.5 hours under ultraviolet light to form a glue layer; then the anode titanium porous transport layer is in direct contact with the proton membrane and compressed evenly. The edge of the anode titanium porous transport layer is supported by a frame, and the cathode titanium porous transport layer and the anode titanium porous transport layer are staggered and superimposed to obtain a PEM hydrogen production membrane electrode assembly.
[0065] Comparative Example 1: Based on Example 2, polypropylene glycol diglycidyl ether is not introduced, and the other processes remain unchanged, specifically:
[0066] Step 1: (1) Add 3.5 parts of silicon nitride and 1.5 parts of 4-aminobutyl triethoxysilane to 35 parts of 45wt% ethanol aqueous solution and mix evenly, then add 1.5 parts of isocyanoethyl methacrylate and react at 30°C for 2.5 hours; wash and dry to obtain modified silicon nitride; (2) Add 15 parts of modified silicon nitride, 5.5 parts of perfluoroalkylethyl acrylate, 1.5 parts of methyl methacrylate, 2.5 parts of N-vinyl carbazole, 5.5 parts of 3-[tri(trimethylsiloxy)silyl]propyl methacrylate, 4.5 parts of 2-acrylic acid, 6-[4-(trans-4-pentylcyclohexyl)phenoxy]hexyl ester, 0.35 parts of azobisisobutyronitrile, and 0.8 parts of octylphenol (3) adding γ-mercaptopropyltrichlorosilane and trimethylchlorosilane in a mass ratio of 2:1 to a 16 wt % isopropanol aqueous solution, stirring at 5 ° C for 1.2 hours, then reacting at 33 ° C for 2 hours, adding isomeric dodecane for extraction, purification, filtration and drying to obtain a mercapto silicone resin; (4) adding 65 parts of polyurethane acrylate, 18 parts of heat-resistant additive filler, 7 parts of mercapto silicone resin, 1.5 parts of acryloxytriisopropylsilane and 0.2 parts of cyclohexyl diphenyl ketone to 165 parts of tetrahydrofuran, stirring evenly in the dark to obtain UV glue;
[0067] Step 2: Cut the base membrane according to the size of the proton membrane to obtain a cathode gasket and an anode gasket for standby use;
[0068] Step 3: stack the cathode gasket, the proton membrane, and the anode gasket, and perform hot pressing at a pressure of 0.3 MPa and a temperature of 125° C. for 75 seconds to obtain a membrane electrode;
[0069] Step 4: After the membrane electrode is filled with UV glue, it is reacted at 40°C for 5.5 hours under ultraviolet light to form a glue layer; then the anode titanium porous transport layer is in direct contact with the proton membrane and compressed evenly. The edge of the anode titanium porous transport layer is supported by a frame, and the cathode titanium porous transport layer and the anode titanium porous transport layer are staggered and superimposed to obtain a PEM hydrogen production membrane electrode assembly.
[0070] Comparative Example 2: Based on Example 2, fluorine, nitrogen and silicon elements are not introduced, and the other processes remain unchanged, specifically:
[0071] Step 1: (1) Add 3 parts of ethylenediamine to 35 parts of 45wt% ethanol aqueous solution and mix evenly, then add 1.5 parts of isocyanoethyl methacrylate and react at 30°C for 2.5 hours; wash and dry to obtain modified silicon nitride; (2) Add 1.5 parts of methyl methacrylate, 4.5 parts of 2-acrylic acid, 6-[4-(trans-4-pentylcyclohexyl)phenoxy]hexyl ester, 0.2 parts of azobisisobutyronitrile, 0.6 parts of octylphenol polyoxyethylene ether, and 0.6 parts of sodium dodecyl sulfate to 60 parts of toluene, react at 75°C for 5.5 hours to obtain a heat-resistant additive filler; (4) Add 65 parts of polyurethane acrylate, 18 parts of heat-resistant additive filler, 9 parts of 1,4-benzenedithiol, 1.5 parts of polypropylene glycol diglycidyl ether, and 0.3 parts of sodium hydroxide to 150 parts of tetrahydrofuran, stir evenly in the dark to obtain UV glue;
[0072] Step 2: Cut the base membrane according to the size of the proton membrane to obtain a cathode gasket and an anode gasket for standby use;
[0073] Step 3: stack the cathode gasket, the proton membrane, and the anode gasket, and perform hot pressing at a pressure of 0.3 MPa and a temperature of 125° C. for 75 seconds to obtain a membrane electrode;
[0074] Step 4: After the membrane electrode is filled with UV glue, it is reacted at 40°C for 5.5 hours under ultraviolet light to form a glue layer; then the anode titanium porous transport layer is in direct contact with the proton membrane and compressed evenly. The edge of the anode titanium porous transport layer is supported by a frame, and the cathode titanium porous transport layer and the anode titanium porous transport layer are staggered and superimposed to obtain a PEM hydrogen production membrane electrode assembly.
[0075] Comparative Example 3, based on Example 2, does not introduce a substance having a structure similar to polyurethane acrylate, and the other processes remain unchanged, specifically:
[0076] Step 1: (1) 5.5 parts of perfluoroalkylethyl acrylate, 1.5 parts of methyl methacrylate, 2.5 parts of N-vinyl carbazole, 5.5 parts of 3-[tri(trimethylsiloxy)silyl]propyl methacrylate, 4.5 parts of 2-acrylic acid, 6-[4-(trans-4-pentylcyclohexyl)phenoxy]hexyl ester, 0.35 parts of azobisisobutyronitrile, 0.8 parts of octylphenol polyoxyethylene ether, and 0.8 parts of sodium dodecyl sulfate were added to 110 parts of toluene and reacted at 75° C. for 5.5 hours to obtain a heat-resistant additive filler; (2) γ-mercaptopropyl tris(2-hydroxyethyl)-1-[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[[ Chlorosilane and trimethylchlorosilane are added to a 16 wt % isopropanol aqueous solution in a mass ratio of 2:1, stirred at 5°C for 1.2 hours, then reacted at 33°C for 2 hours, and extracted with isododecane, purified, filtered, and dried to obtain a mercapto silicone resin; (3) 65 parts of polyurethane acrylate, 18 parts of heat-resistant added filler, 9 parts of mercapto silicone resin, 1.5 parts of polypropylene glycol diglycidyl ether, 1.5 parts of acryloxy triisopropyl silane, and 0.2 parts of cyclohexyl diphenyl ketone are added to 165 parts of tetrahydrofuran, stirred evenly in the dark, and a UV glue is obtained;
[0077] Step 2: Cut the base membrane according to the size of the proton membrane to obtain a cathode gasket and an anode gasket for standby use;
[0078] Step 3: stack the cathode gasket, the proton membrane, and the anode gasket, and perform hot pressing at a pressure of 0.3 MPa and a temperature of 125° C. for 75 seconds to obtain a membrane electrode;
[0079] Step 4: After the membrane electrode is filled with UV glue, it is reacted at 40°C for 5.5 hours under ultraviolet light to form a glue layer; then the anode titanium porous transport layer is in direct contact with the proton membrane and compressed evenly. The edge of the anode titanium porous transport layer is supported by a frame, and the cathode titanium porous transport layer and the anode titanium porous transport layer are staggered and superimposed to obtain a PEM hydrogen production membrane electrode assembly.
[0080] Comparative Example 4, based on Example 2, does not introduce the organosilicon derivative, and the other processes remain unchanged, specifically:
[0081] Step 1: (1) Add 3.5 parts of silicon nitride and 1.5 parts of 4-aminobutyl triethoxysilane to 35 parts of 45wt% ethanol aqueous solution and mix evenly, then add 1.5 parts of isocyanoethyl methacrylate and react at 30°C for 2.5 hours; wash and dry to obtain modified silicon nitride; (2) Add 15 parts of modified silicon nitride, 5.5 parts of perfluoroalkylethyl acrylate, 1.5 parts of methyl methacrylate, 2.5 parts of N-vinyl carbazole, 5.5 parts of 3-[tri(trimethylsiloxy)silyl]propyl methacrylate, 4.5 parts of 2-acrylic acid, 6-[4-(trans-4-pentylcyclohexyl)phenoxy]hexyl ester, 0.35 parts of azobisisobutyronitrile, and 0.8 parts of octylphenol polyoxyethylene ether. , 0.8 parts of sodium dodecyl sulfate are added to 110 parts of toluene, and reacted at 75°C for 5.5 hours to obtain a heat-resistant additive filler; (3) γ-mercaptopropyltrichlorosilane and trimethylchlorosilane are added to a 16wt% isopropanol aqueous solution in a mass ratio of 2:1, stirred at 5°C for 1.2 hours, and then reacted at 33°C for 2 hours, and isomeric dodecane is added for extraction, purification, filtration and drying to obtain a mercapto silicone resin; (4) 65 parts of polyurethane acrylate, 18 parts of heat-resistant additive filler, 12 parts of 1,4-benzenedithiol, 2 parts of divinylbenzene, 1.5 parts of polypropylene glycol diglycidyl ether, and 0.2 parts of cyclohexyl diphenyl ketone are added to 165 parts of tetrahydrofuran, and stirred evenly in the dark to obtain a UV glue;
[0082] Step 2: Cut the base membrane according to the size of the proton membrane to obtain a cathode gasket and an anode gasket for standby use;
[0083] Step 3: stack the cathode gasket, the proton membrane, and the anode gasket, and perform hot pressing at a pressure of 0.3 MPa and a temperature of 125° C. for 75 seconds to obtain a membrane electrode;
[0084] Step 4: After the membrane electrode is filled with UV glue, it is reacted at 40°C for 5.5 hours under ultraviolet light to form a glue layer; then the anode titanium porous transport layer is in direct contact with the proton membrane and compressed evenly. The edge of the anode titanium porous transport layer is supported by a frame, and the cathode titanium porous transport layer and the anode titanium porous transport layer are staggered and superimposed to obtain a PEM hydrogen production membrane electrode assembly.
[0085] Testing experiment: The performance of a PEM hydrogen production membrane electrode assembly of Examples 1 to 4 and Comparative Examples 1 to 4 was tested: (1) Insulation performance test: The resistivity of the proton membrane of a PEM hydrogen production membrane electrode assembly of Examples 1 to 4 and Comparative Examples 1 to 4 was tested with reference to GB / T 1692-2008. The test results are shown in Table 1; (2) High temperature immersion sealing test: A PEM hydrogen production membrane electrode assembly of Examples 1 to 4 and Comparative Examples 1 to 4 was fixed at a height of 1.5 meters from the water surface and left to stand at 25°C for one day, and then a sealing test was performed after reflow soldering at 260°C. The potassium permanganate powder was tested for discoloration. The test results are shown in Table 1;
[0086]
[0087]
[0088] Table 1
[0089] Result analysis: According to the data analysis in Table 1, in order to improve the high temperature resistance, the scheme adopts modified prepolymer and introduces elements such as fluorine, nitrogen, and silicon, which effectively prevents the failure of the glue at high temperature. Secondly, in order to enhance the insulation performance, the scheme introduces high temperature resistant and insulating silicon nitride as an inorganic filler, which further improves the stability and high transmittance of the UV glue.
[0090] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A PEM hydrogen production membrane electrode assembly, characterized in that: It includes an anode gasket, a cathode gasket, a proton membrane, and UV glue; the proton membrane is arranged between the anode gasket and the cathode gasket; the cathode gasket includes a cathode gasket outer frame and a cathode gasket inner frame; the anode gasket includes an anode gasket outer frame and an anode gasket inner frame.
2. A PEM hydrogen production membrane electrode assembly according to claim 1, characterized in that: The size of the cathode gasket inner frame is larger than the proton membrane; the size of the anode gasket inner frame is smaller than the proton membrane.
3. A method for preparing a PEM hydrogen production membrane electrode assembly, characterized in that: A method for preparing a PEM hydrogen production membrane electrode assembly according to any one of claims 1 to 2, comprising the following steps: Step 1: Cut the base membrane according to the size of the proton membrane to obtain a cathode gasket and an anode gasket for standby use; Step 2: stack the cathode gasket, the proton membrane, and the anode gasket, and hot-press at 100 to 150° C. for 30 to 120 seconds to obtain a membrane electrode; Step 3: Fill the membrane electrode with UV glue and solidify it to form a glue layer; then tightly connect the anode titanium porous transport layer and the cathode titanium porous transport layer to the proton membrane on both sides of the proton membrane to assemble the electrolyzer to obtain a PEM hydrogen production membrane electrode assembly.
4. The method for preparing a PEM hydrogen production membrane electrode assembly according to claim 3, characterized in that: The material of the base film includes one of polyimide, polyethylene terephthalate, polyethylene naphthalate, and polyphenylene sulfide.
5. The method for preparing a PEM hydrogen production membrane electrode assembly according to claim 3, characterized in that: The preparation process of the assembled electrolytic cell is specifically as follows: after the glue layer is formed, the anode titanium porous transport layer is in direct contact with the proton membrane and is compressed evenly, the edge of the anode titanium porous transport layer is supported by a frame, and the cathode titanium porous transport layer and the anode titanium porous transport layer are staggered and superimposed.
6. The method for preparing a PEM hydrogen production membrane electrode assembly according to claim 3, characterized in that: The specific preparation process of the UV glue is as follows: Step 1: (1) adding silicon nitride and 4-aminobutyltriethoxysilane to a 40-50 wt% ethanol aqueous solution and mixing them evenly, then adding isocyanoethyl methacrylate and reacting them at 25-35° C. for 2-3 hours; washing and drying to obtain modified silicon nitride; (2) adding modified silicon nitride, perfluoroalkylethyl acrylate, methyl methacrylate, N-vinyl carbazole, 3-[tri(trimethylsiloxy)silyl]propyl methacrylate, 2-acrylic acid, 6-[4-(trans-4-pentylcyclohexyl)phenoxy]hexyl ester, azobisisobutyronitrile, octylphenol polyoxyethylene ether, and sodium dodecyl sulfate to toluene, reacting them at 70-80° C. for 5-6 hours to obtain a heat-resistant added filler; Step 2: Add polyurethane acrylate, heat-resistant additive filler, mercapto silicone resin, polypropylene glycol diglycidyl ether, acryloxy triisopropyl silane, and cyclohexyl diphenyl ketone to tetrahydrofuran, and stir evenly in a dark place to obtain UV glue.
7. The method for preparing a PEM hydrogen production membrane electrode assembly according to claim 3, characterized in that: The specific process of the curing process is: after the membrane electrode is filled with UV glue, it reacts at 30-50° C. for 5-6 hours under ultraviolet light.
8. The method for preparing a PEM hydrogen production membrane electrode assembly according to claim 6, characterized in that: The raw materials of the UV glue include the following components: by mass, 60 to 70 parts of polyurethane acrylate, 15 to 22 parts of heat-resistant additive filler, 8 to 10 parts of mercapto silicone resin, 1 to 2 parts of polypropylene glycol diglycidyl ether, 1 to 2 parts of acryloxy triisopropyl silane, 0.1 to 0.3 parts of cyclohexyl diphenyl ketone, and 150 to 180 parts of tetrahydrofuran.
9. The method for preparing a PEM hydrogen production membrane electrode assembly according to claim 6, characterized in that: The raw materials of the modified silicon nitride include the following components: 3-4 parts of silicon nitride, 1-2 parts of 4-aminobutyltriethoxysilane, 30-40 parts of 40-50wt% ethanol aqueous solution, and 1-2 parts of isocyanoethyl methacrylate, by weight. The raw materials of the heat-resistant additive filler include the following components: by mass, 15 parts of modified silicon nitride, 5 to 6 parts of perfluoroalkylethyl acrylate, 1 to 2 parts of methyl methacrylate, 2 to 3 parts of N-vinyl carbazole, 5 to 6 parts of 3-[tris(trimethylsiloxy)silyl]propyl methacrylate, 4 to 5 parts of 2-acrylic acid, 6-[4-(trans-4-pentylcyclohexyl)phenoxy]hexyl ester, 0.2 to 0.5 parts of azobisisobutyronitrile, 0.5 to 1 parts of octylphenol polyoxyethylene ether, 0.5 to 1 parts of sodium dodecyl sulfate, and 100 to 120 parts of toluene.